Language shift and maintenance: a case study of Kani Tribes - KM, Shreelakshmi (Nepalese Linguistics, 2019)
This paper aims to look into the status of the language maintenance and shifts in the Malampasha, a language spoken by the Kanikkar (ISO 639-3, kev) community in Kerala. The paper also intends to draw out some of the struggles that the Kanikkar community face in the wake of the dominating presence of Malayalam.